2011
DOI: 10.1016/j.ijmedinf.2011.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Design and implementation of I2Vote – An interactive image-based voting system using windows mobile devices

Abstract: An easy to use handheld based ARS that enables interactive, image-based, teaching is achieved. The system effectively adds an extra dimension to the use of an ARS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Among the customized tools and applications (n = 9) Radiation Protection (RP) module improved radiation protection knowledge [16], Radiological Ordering Module (ROM) improved quality of radiologic examination orders [17], I2Vote improved knowledge retention [18], and Online Electronic Information Skills OEIS developed skills in accessing the right radiology information [19]. The Learning Virtual Object LVO is seen to be of no importance in changing student performance but it did give significant results if used for longer duration [20].…”
Section: E-learning Initiativesmentioning
confidence: 99%
See 2 more Smart Citations
“…Among the customized tools and applications (n = 9) Radiation Protection (RP) module improved radiation protection knowledge [16], Radiological Ordering Module (ROM) improved quality of radiologic examination orders [17], I2Vote improved knowledge retention [18], and Online Electronic Information Skills OEIS developed skills in accessing the right radiology information [19]. The Learning Virtual Object LVO is seen to be of no importance in changing student performance but it did give significant results if used for longer duration [20].…”
Section: E-learning Initiativesmentioning
confidence: 99%
“…Audience Response System ARS has shown useful results in other medical and non medical fields [18] but its use is limited in the radiology education because of its intense image based nature. In [18], use of audience response system I2vote for radiology education was ranked 4.2 by students on a five point Likert-scale in terms of usability and 3.8 in terms of its image based interaction capabilities.…”
Section: Level 1: Learner Satisfactionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was observed that the use of an SRS (called i-SIDRA) by a large number of medical students enrolled in an anatomy of the locomotor system course improved medical degree students' performance [23]. Other researchers have revealed emergence of using SRSs and designing of wide range of customized tools according to learner needs assessment in radiology education [21,83,84]. An interesting study was designed by Johansson et al [85], in which several speech-language pathologists listen a playback of recordings of a set of speakers, then using an SRS to distinguish speakers with cervical spinal cord injuries from non-injured speakers.…”
Section: Medical and Health Sciencesmentioning
confidence: 99%
“…Additionally, the students can include questions, comments, doubts, suggestions or incidences occurred in classroom that are later analyzed by the teacher [15]. Kahoot [16], NetClick [17], Socrative [18], VotApedia [19], Poll Everywhere [20], i2Vote [21], iClickers [22], i-SIDRA [23], Mentimeter [24], and Quizizz [25] are some examples of software tools that implement SRSs in a simply and fast way. Some studies even suggest that SRSs can be conveniently implemented using Twitter and other social networks [26].…”
Section: Introductionmentioning
confidence: 99%